Folate-deficiency induced acyl-CoA synthetase short-chain family member 2 increases lysine crotonylome involved in neural tube defects - Wang, Shan; Zeng, Yubing; He, Xuejia; Liu, Fan; Pei, Pei; Zhang, Ting (Frontiers in Molecular Neuroscience, 2023)
Maternal folate deficiency increases the risk of neural tube defects (NTDs), but the mechanism remains unclear. Here, we established a mouse model of NTDs via low folate diets combined with MTX-induced conditions. We found that a significant increase in butyrate acid was observed in mouse NTDs brains. In addition, aberrant key crotonyl-CoA-producing enzymes acyl-CoA synthetase short-chain family member 2 (ACSS2) levels and lysine crotonylation (Kcr) were elevated high in corresponding low folate content maternal serum samples from mouse NTD model. Next, proteomic analysis revealed that folate deficiency led to global proteomic modulation, especially in key crotonyl-CoA-producing enzymes, and dramatic ultrastructural changes in mouse embryonic stem cells (mESCs). Furthermore, we determined that folate deficiency induced ACSS2 and Kcr in mESCs. Surprisingly, folic acid supplementation restored level of ACSS2 and Kcr. We also investigated overall protein post-translational Kcr under folate deficiency, revealing the key regulation of Kcr in glycolysis/gluconeogenesis, and the citric acid cycle. Our findings suggest folate deficiency leads to the occurrence of NTDs by altering ACSS2. Protein crotonylation may be the molecular basis for NTDs remodeling by folate deficiency.